STRATEGI PEMASARAN DIGITAL PADA INDUSTRI SKINCARE MELALUI PLATFORM TIKTOK - Muhammad Fauzan; Siti Aisyah (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to examine effective digital marketing strategies in the skincare industry through the TikTok platform. In an increasingly digital era, social media platforms have become an important means for skincare companies to promote their products and reach a wider target market. TikTok, as a popular social media platform, provides significant opportunities for skincare companies to reach younger audiences and engage in creative marketing campaigns. This research will use qualitative and quantitative methods to analyze successful digital marketing strategies on TikTok. Data will be collected through interviews with digital marketing experts, consumer surveys, and analysis of TikTok content that has been carried out by skincare companies. In addition, this research will also examine trends and characteristics of TikTok users that are relevant to the skincare industry. It is hoped that the research results will provide in-depth insight into effective digital marketing strategies through TikTok, including the most effective types of content, optimal posting frequency, and how to interact with the audience. In addition, this research will provide practical recommendations to skincare companies who want to exploit the potential of TikTok to increase the visibility and sales of their products. This research will contribute to the understanding of digital marketing in the skincare industry and provide useful guidance for marketing practitioners looking to optimize their presence on TikTok. Thus, it is hoped that this research will help skincare companies to achieve greater success in the ever-changing digital marketing environment.